2013
DOI: 10.2169/internalmedicine.52.0168
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Laboratory Factors in the Differential Diagnosis of Tuberculous and Cryptococcal Meningitis in Adult HIV-negative Patients

Abstract: Objective It is difficult to make the differential diagnosis between tuberculous meningitis (TBM) and cryptococcal meningitis (CM) when the smear is negative. The objective of this study was to create a diagnostic rule for differentiating TBM from CM in adult HIV-negative patients based on clinical and laboratory features. Methods The clinical and laboratory data of 219 adult HIV-negative patients satisfying the diagnostic criteria for tuberculous (n=100) and cryptococcal (n=119) meningitis hospitalized at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 21 publications
3
8
0
Order By: Relevance
“…However, CM patients were more likely to suffer headache, vision and hearing damage, TBM patients were more prone to have fever and cough. These results were fairly consistent with previous reports [9, 17, 18]. One review showed headache (87%), fever (74%), meningeal irritation (67%), vomiting (61%) and altered mentation (26%) as the most common clinical manifestations of CM [9].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…However, CM patients were more likely to suffer headache, vision and hearing damage, TBM patients were more prone to have fever and cough. These results were fairly consistent with previous reports [9, 17, 18]. One review showed headache (87%), fever (74%), meningeal irritation (67%), vomiting (61%) and altered mentation (26%) as the most common clinical manifestations of CM [9].…”
Section: Discussionsupporting
confidence: 92%
“…Patients with TBM presented with higher CSF WBC and total protein than CM patients, similar to prior studies [18]. A low ratio of CD4/CD8 was also found in the apparently healthy CM patients, it’s possible those patients may have some undetectable underlying disease.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Clinicians should also pay attention to check the existence of C. neoformans through CSF examination. To improve the positive rate, repeated examinations of the CSF for C. neoformans must be carried out [17]. However, this method is often limited when the number of the fungus is too few to be identified.…”
Section: Discussionmentioning
confidence: 99%